Operational Management For Closure And Reclamation -- Kennecott Ridgeway Mine (434d9e8f-c312-47a7-bf26-a20c5fc01595) - R. Dorey (Society for Mining, Metallurgy & Exploration, 1999)
The Kennecott Ridgeway Mine in South Carolina is scheduled to complete mining and ore processing in the last quarter of 1999. Tailings are disposed in a 300 acre, lined tailings impoundment. To facilitate closure and reclamation, modification of the tailings impoundment operation has been adopted. Mining involved the sequenced development of two open pits. In 1996 mining of the South Pit was completed and backfilling of the pit with waste rock from the North Pit was initiated and will continue until mining ceases. Both pits will be reclaimed as fresh water lakes. This paper presents the physical, geochemical and hydrogeochemical evaluation of the operational and post operational management of the project. Comparison of the operational monitoring data against predicted performance is reviewed.